Penggunaan Kata Tabu dalam Tuturan Pembaca Berita “Pojok Kampung” JTV - Andriani, Viena Wanidha (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This research aims to describe the types and examples of taboo words used by news readers on JTV's